Lack of CD117 and rare bcl-2 expression in stomach cancer by immunohistochemistry. An immunohistochemical study with review of the literature - Mireskandari Masoud; Shafaii Ali; Kayser Gian; Kayser Klaus (BMC, 2006)
Abstract Background Gastric adenocarcinoma is one of the most frequent malignancies worldwide including Iran. This study was designed to immunohistochemically evaluate the CD117 and bcl-2 expression in gastric carcinomas and their potential use as therapeutic targets in the treatment of patients with advanced stage gastric cancer. Materials and methods Representative paraffin blocks obtained from 38 operated gastric adenocarcinoma patients were retrieved from Afzalipour Hospital pathology department archive, Kerman, Iran. Immunohistochemical analysis (IHC) for CD117 was carried out in all cases including negative (normal gastric epithelium) and positive (Gastrointestinal Stromal Tumor) controls. In addition, the cases were evaluated immunohistochemically for apoptosis-related protein (bcl-2), to evaluating a potential association of CD117 expression with the cell proliferation regulatory pathways. Results No positive reaction for CD117 was seen in gastric carcinoma tumor cells irrespective to the cell type, grade, and stage, proliferation and apoptosis rate. Expression of bcl-2 was observed in only one case. Conclusion We conclude that CD117 overexpression detectable by immunohistochemistry does not play a significant role in gastric carcinoma pathways and development, although overexpression at the gene level and/or mutated CD117 expression might exist. Thus, it is unlikely that the CD117 pathway is of clinical significance in gastric carcinoma patients.